2005
DOI: 10.1103/physrevb.72.115314
|View full text |Cite
|
Sign up to set email alerts
|

MetallicSi(111)(7×7)-reconstruction: A surface close to a Mott-Hubbard metal-insulator transition

Abstract: Li adsorption at extremely low coverages ͑10 −3 ML and below͒ on the metallic Si͑111͒-͑7 ϫ 7͒ surface has been studied by ␤-NMR experiments ͑measurement of T 1 -times͒. Instead of increasing linearly with the sample temperature, as expected for a metallic system, the relaxation rate ␣ =1/T 1 is almost constant in between 50 K and 300 K sample temperature and rises considerably above. Comparison with T 1 -times around 900 K ͑ob-served with 6 Li-NMR͒ excludes adsorbate diffusion as the cause of the relaxation ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
10
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 72 publications
4
10
0
Order By: Relevance
“…According to this comparison, Si111-7 7 is clearly not in the metallic range. This finding appears consistent with a recent temperaturedependent and surface sensitive NMR study of Si111-7 7, which suggested that the surface is close to a Mott-Hubbard-type metal insulator transition [13] and it could also be related to the strong electron-phonon coupling [14].…”
supporting
confidence: 92%
“…According to this comparison, Si111-7 7 is clearly not in the metallic range. This finding appears consistent with a recent temperaturedependent and surface sensitive NMR study of Si111-7 7, which suggested that the surface is close to a Mott-Hubbard-type metal insulator transition [13] and it could also be related to the strong electron-phonon coupling [14].…”
supporting
confidence: 92%
“…It has also been reported that Si͑111͒7 ϫ 7 is likely a surface close to a Mott-Hubbard metal-insulator transition. 30,31 Accurate determination of the detailed adatom-state band structure as well as theoretical estimations of the conductance by much sophisticated model such as the Kubo formula is highly requested.…”
Section: IImentioning
confidence: 99%
“…Another possible reasons for a gap at E F are structural distortions such as charge density waves. There is no theoretical estimation of the Mott-Hubbard or charge density wave gap for the Si(111)-(7x7) surface, and the experimental data from high-resolution photoemission [7], high-resolution electron-energy-loss spectroscopy [8], nuclear magnetic resonance [9] and transport measurements [10,11] hint to a gap between 0 eV and a few tenths of an eV at low temperatures. These values are well below the minimum gap reported from the published STS data.…”
mentioning
confidence: 99%